Capture history of humpback whales in the Kitimat Fjord System, 2004–2019. - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
Capture history of humpback whales in the Kitimat Fjord System, 2004–2019.